2008
DOI: 10.1177/1475921708089830
|View full text |Cite
|
Sign up to set email alerts
|

Time-Frequency Method for Nonlinear System Identification and Damage Detection

Abstract: This paper presents a method for extracting system nonlinearities and time-localized transient response to impulsive loading by processing stationary/transient responses using the Hilbert—Huang transform (HHT) and a sliding-window fitting (SWF) technique. Time-dependent dynamic characteristics of nonlinear systems are derived using perturbation analysis. The SWF is introduced mainly to show the mathematical implications of HHT and the differences between HHT and the discrete Fourier transform. Similar to the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…On the other hand, the amplitude 2 A is attenuated by the concrete material to 730. The nonzero residual 2 r (blue) indicates that there is quadratic nonlinearity 22 , and it is believed to be caused by the contact condition between the sensor and the concrete. Figures 5-9 shows the results of Cases C05-2 to C05-6.…”
Section: Active Modulation Testing and Time-frequency Modulation Analmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, the amplitude 2 A is attenuated by the concrete material to 730. The nonzero residual 2 r (blue) indicates that there is quadratic nonlinearity 22 , and it is believed to be caused by the contact condition between the sensor and the concrete. Figures 5-9 shows the results of Cases C05-2 to C05-6.…”
Section: Active Modulation Testing and Time-frequency Modulation Analmentioning
confidence: 97%
“…Moreover, the large variations of 1 ω and 1 2 / ω ω indicates that the 100k Hz probe is significantly modulated by the damage-induced nonlinearities. 22 The experimental results reveal that changes and variations of amplitudes and frequency ratio are good damage indicators, but it is difficult to estimate damage because the response amplitude under a fixed-frequency harmonic excitation highly depends on the closeness of the excitation frequency to a natural frequency. It is believed that, for damage estimation, one needs to use one or two excitation frequencies defined with respect to a selected natural frequency after damage or use a periodic chirp excitation or a random excitation, which is the topic under current investigation.…”
Section: Active Modulation Testing and Time-frequency Modulation Analmentioning
confidence: 98%
“…For the specific case of a parametrically excited cantilever beam, there have been extensive analytical studies conducted on this problem [9][10][11][12]. Unfortunately, experimental works on these systems are few and qualitative discrepancies have been shown to occur between theory and experiment [13,14].…”
Section: Introductionmentioning
confidence: 97%
“…Despite a quite large use of this technique in several fields of digital signal processing (Pai et al, 2007;Schmitt et al, 2007;Sweeney-Reed and Nasuto, 2007) only a few examples have been shown in geophysical data processing Battista et al, 2007Battista et al, , 2009Magrin-chagnolleau and Baraniuk, 1999).…”
Section: Introductionmentioning
confidence: 99%